Adaptation Strategies followed by the Rice Growers to Mitigate the Impact of Climate Change - Palani, Suganthkumar; H, Philip (Journal of Extension Education, 2018)
The study was conducted in Orathanadu block of Thanjavur district in Tamil Nadu. Proportionate random sampling was employed to select the sample. It was observed that the variables viz., educational status and fatalism showed positive significant correlation at one per cent level of probability whereas awareness on climate change showed negative correlation. Variables like annual income, extension agency contact and awareness on crop insurance showed negative correlation at five per cent level of probability